FOREGROUNDING DIVERSE AFRICAN SEXUALITIES - Frizelle, Kerry (PINS-Psychology in Society, 2025)
Gunkel, Henriette (2010) The cultural politics of female sexuality in South Africa. New York & London: Routledge. ISBN 978-0-415-89555-2 pbk. Pages xii + 181. In her book, The cultural politics of female sexuality in South Africa, Gunkel develops a comprehensive analysis that powerfully illustrates the complex ways in which sexuality is socially and historically constructed. In particular it highlights the importance of the concept of “intersectionality”, which emphasises the varied and complex ways in which a number of “social positionalities” (or “axes of social power”) such as politics, gender, race and sexuality intersect, shape and constitute each other (Steyn & van Zyl, 2012: 8-9). More specifically it highlights the importance of what Steyn and van Zyl (2012: 9) refer to as “a politics of location”, that is, a recognition of the way in which sexualities are constituted in particular ways in particular socio-historical locations. In this way the overall project of Gunkel’s book is, in her own words, “centered around, and seeks to account for, the sexual politics that have emerged out of post-apartheid South Africa” (p 4).